Synthesis and structure-activity relationships of carbohydrazides and 1,3,4-oxadiazole derivatives bearing an imidazolidine moiety against the yellow fever and dengue vector, Aedes aegypti - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (JOHN WILEY & SONS LTD, 2018)
BACKGROUND 1,3,4-Oxadiazole and imidazolidine rings are important heterocyclic compounds exhibiting a variety of biological activities. In this study, novel compounds with oxadiazole and imidazolidine rings were synthesized from 3-(methylsulfonyl)-2-oxoimidazolidine-1-carbonyl chloride and screened for insecticidal activities. The proposed structures of the 17 synthesized compounds were confirmed using elemental analysis, infrared (IR), proton nuclear magnetic resonance (H-1-NMR), and mass spectroscopy. RESULTS None of the compounds showed larvicidal activity at the tested concentrations against first-instar Aedes aegypti larvae. However, nine compounds exhibited promising adulticidal activity, with mortality rates of >= 80% at 5 mu g per mosquito. Further dose-response bioassays were undertaken to determine median lethal dose (LD50) values. Compounds 1, 2b, 2c, 2d, 2 g, 3b, 3c, 3 g, and 3 h were effective, with typical LD50 values of about 5 - 10 mu g per mosquito against female Ae. aegypti. Compounds 2c (bearing a nitro group on the aromatic ring; LD50 = 2.80 0.54 mu g per mosquito) and 3 h (double halogen groups at 2,4 position on the phenyl ring; LD50 = 2.80 +/- 0.54 mu g per mosquito) were the most promising compounds. CONCLUSION Preliminary mode of action studies failed to show consistent evidence of either neurotoxic or mitochondria-directed effects. Further chemical synthesis within this series may lead to the development of new effective insecticides. (C) 2017 Society of Chemical Industry
Keywords: insecticide; mosquitocidal activity; mosquito control; carbohydrazide and amide; mitochondria; INSECTICIDAL ACTIVITY; DESIGN; ANTICANCER; INHIBITORS; OXADIAZOLE; AGENTS; RINGS; MODE